Answer:Simplifying
3k + 9 + -1k + -17 = 0
Reorder the terms:
9 + -17 + 3k + -1k = 0
Combine like terms: 9 + -17 = -8
-8 + 3k + -1k = 0
Combine like terms: 3k + -1k = 2k
-8 + 2k = 0
Solving
-8 + 2k = 0
Solving for variable 'k'.
Move all terms containing k to the left, all other terms to the right.
Add '8' to each side of the equation.
-8 + 8 + 2k = 0 + 8
Combine like terms: -8 + 8 = 0
0 + 2k = 0 + 8
2k = 0 + 8
Combine like terms: 0 + 8 = 8
2k = 8
Divide each side by '2'.
k = 4
Simplifying
k = 4
Explanation: